Spatial–Temporal Characteristics and Driving Mechanisms of Land–Use Transition from the Perspective of Urban–Rural Transformation Development: A Case Study of the Yangtze River Delta - Xing Niu; Fenghua Liao; Ziming Liu; Guancen Wu (Land, 2022)
Urban–rural transformation development is the key to resolving the imbalance in the dual structure of urban and rural areas. However, the transformation of the urban–rural relationship will also affect the structure and spatial distribution of land use. This paper measured the spatial–temporal characteristics of land–use transition in the Yangtze River Delta from 1990 to 2018 by using a geo–information Tupu method and explored the driving mechanism of land–use transition under the background of urban–rural transformation development by using a spatial regression analysis method. The results showed the following: (1) The transition from cultivated land to urban construction land, from rural residential land to cultivated land, and from rural residential land to urban construction land were the three main types of land–use transition in the Yangtze River Delta during urban–rural transformation development. (2) The transition from cultivated land to urban construction land was always the most important type of land–use transition. It expanded from the central area to the surrounding cities. The transition of rural residential land to cultivated land and urban construction land began to increase significantly after the year 2010, which was the urban–rural integration development period. (3) The urban–rural land–use transition was driven by government policies, industrial restructuring, population urbanization and migration. During the urban–rural integration development period, secondary industry and tertiary industry were the main driving factors of the transition from cultivated land to urban construction land. The number of policies, the primary industry, the total population, and the urbanization rate were the main driving factors of the transition from rural residential land to cultivated land. Primary industry, secondary industry, and tertiary industry were the main driving factors of the transition from rural residential land to urban construction land. Finally, the study provided some suggestions for policy, industry, and population driving forces.